2020
DOI: 10.1007/s00484-020-01921-0
|View full text |Cite
|
Sign up to set email alerts
|

Hot and cold weather based on the spatial synoptic classification and cause-specific mortality in Sweden: a time-stratified case-crossover study

Abstract: The spatial synoptic classification (SSC) is a holistic categorical assessment of the daily weather conditions at specific locations; it is a useful tool for assessing weather effects on health. In this study, we assessed (a) the effect of hot weather types and the duration of heat events on cardiovascular and respiratory mortality in summer and (b) the effect of cold weather types and the duration of cold events on cardiovascular and respiratory mortality in winter. A time-stratified case-crossover design com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 78 publications
(138 reference statements)
1
4
0
Order By: Relevance
“…These results in which the estimated pooled overall heat effects are larger for respiratory than CVD mortality, are consistent with other studies (27). In our study, we did not identify a significant increase in cardiovascular mortality due to heat, similarly to this multi-city study (28); however, another found a clear high effect in southern Swedish locations and not in the northern ones (29).…”
Section: Discussionsupporting
confidence: 93%
“…These results in which the estimated pooled overall heat effects are larger for respiratory than CVD mortality, are consistent with other studies (27). In our study, we did not identify a significant increase in cardiovascular mortality due to heat, similarly to this multi-city study (28); however, another found a clear high effect in southern Swedish locations and not in the northern ones (29).…”
Section: Discussionsupporting
confidence: 93%
“…Each day with events was matched with its control days according to the year, month, and day of the week by including a stratum variable in the model. As previous studies have shown, the short-term effect of temperature on health can be not linear with increased risks in heat and cold ranges, and also not limited to the same day of exposure with effects still persisting for several days [ 9 , 10 , 12 , 27 , 28 ]. Although the current literature on mental health hospitalizations and temperature suggests a potential linear association, we chose to explore potential non-linearities using distributed lag non-linear models, a flexible framework that allows us to compare different parametrizations of the exposure-response association and account for lagged dependencies [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The relevant calculation formulas are summarized in Table 2 , except for “Perceived Temperature” [ 39 ] as it was not provided in the relevant study. Only one study [ 74 ] used air masses (excluding air TEMP) to define heat days.…”
Section: Resultsmentioning
confidence: 99%